Employment and unemployment in Germany: Some results from a macroeconomic disequilibrium model - Werner Smolny (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
In the paper, some empirical results from a macroeconometric disequilibrium model for the Federal Republic of Germany are reported. In the theoretical model, a delayed adjustment of employment and investment is analyzed. Market disequilibrium is introduced by allowing for a sluggish adjustment of wages and prices. The estimation results reveal the importance of the slow adjustment of prices and quantities for the employment Situation in Germany. The slow adjustment of employment and the capital stock contributed to the persistence of unemployment in the second half of the eighties.
Keywords: E24; E32; 330; (un)-employment; macroeconometric disequilibrium model